First report of naturally infected Aedes aegypti with chikungunya virus genotype ECSA in the Americas. - André Luis Costa-; Rafaella Sayuri Ioshino; Vivian Petersen; Antonio Fernando Lima; Marielton Dos Passos Cunha; Michael R Wiley; Jason T Ladner; Karla Prieto; Gustavo Palacios; Danuza Duarte Costa; Lincoln Suesdek; Paolo Marinho de Andrade Zanotto; et al. (Public Library of Science (PLoS), 2017)
The worldwide expansion of new emergent arboviruses such as Chikungunya and Zika reinforces the importance in understanding the role of mosquito species in spreading these pathogens in affected regions. This knowledge is essential for developing effective programs based on species specificity to avoid the establishment of endemic transmission cycles sustained by the identified local vectors. Although the first autochthonous transmission of Chikungunya virus was described in 2014 in the north of Brazil, the main outbreaks were reported in 2015 and 2016 in the northeast of Brazil.During 5 days of February 2016, we collected mosquitoes in homes of 6 neighborhoods of Aracaju city, the capital of Sergipe state. Four mosquito species were identified but Culex quinquefasciatus and Aedes aegypti were the most abundant. Field-caught mosquitoes were tested for Chikungunya (CHIKV), Zika (ZIKV) and Dengue viruses (DENV) by qRT-PCR and one CHIKV-infected Ae. aegypti female was detected. The complete sequence of CHIKV genome was obtained from this sample and phylogenetic analysis revealed that this isolate belongs to the East-Central-South-African (ECSA) genotype.Our study describes the first identification of a naturally CHIKV-infected Ae. aegypti in Brazil and the first report of a CHIKV from ECSA genotype identified in this species in the Americas. These findings support the notion of Ae. aegypti being a vector involved in CHIKV outbreaks in northeast of Brazil.